Dimensional Calculation of Automatic Soldering Station Chain Conveyor's Electric Motor - Blatnický, Miroslav; Dižo, Ján; Kurčík, Pavol; Blatnická, Mária (Manufacturing Technology Journal, 2018)
The paper deals with a design of required electric motor power for the conveyor line. This machine will serve for automatic soldering of a compressor outlet piping in a real company. The calculation of the motor is necessary to ensure a required handling of pallets with the compressors, i.e. between individual working positions. These positions consist of manual loading components on the line, automatic soldering and manual tightness control. After determining the power of the drive motor, it will be possible to produce a real prototype. The designed electric motor will be integrated into the machine and that will demonstrate the correctness of all design suggestions and calculations including the dimensional calculation of the drive motor in conjunction with the customer's technical standards requirements.
Keywords: Chain conveyor; soldering station; dimensional calculation; electric motor